LIFE-THREATENING BURNS CAUSED BY HOUSEHOLD CHEMICALS - K. M. Krylov; D. O. Vagner; E. V. Zinoviev; K. E. Michunsky; V. N. Yurina (Неотложная медицинская помощь, 2018)
Background Chemical burns are 2.5 % to 5.1% of all burn injuries. Burns caused with household chemicals occur even more rarely. Because of its relative rarity there is no common surgical tactics for such patients. This type of burn trauma still remains under discussion. Aim of study Optimization of surgical treatment tactics in patients with severe chemical burns caused by household chemicals. Material and methods Medical histories of patients with life-threatening burns, caused by household chemicals. Results In order to remove the damaging agent, multiple incisions were performed as early as possible after admission. After stabilization, necrotized tissue was removed gradually to the superficial fascia. Single-stage autografting was considered unreasonable due to the lack of objective factors of the lesion depth. Hydrocolloid dressings were used for temporal closure of wounds. As tissues became clean we covered granulating wound by split-skin grafts. Conclusion Early fascial excision and delayed autoplasty is the priority method of surgical treatment of patients with life-threatening burns caused by household chemicals.